Crisis and Utopia: André Gorz and the end of work. (May 2023) - Granter, Edward; Aroles, Jeremy
In this paper, we are concerned with the role of André Gorz in the development of the concept of the end of work. We draw from Gorz's stance on automation, utopia, capitalism and labour to reflect on the directions of the end of work debate, leaning towards Gorz's invitation to repoliticize the end of work. While Gorz's writings predate the rise of the gig economy, he presaged many of the developments we are currently witnessing. Even if the end of work is not in sight, we argue that it remains nonetheless a useful concept to help us cultivate possibilities and a sense of difference. Finally, it is our intention to highlight that while Gorz's work received less attention than other scholars broadly associated with critical examinations of capitalism, his scholarship holds the potential to reinvigorate, or rejuvenate, debates pertaining to the end of work as well as the future of work.